Case study on application of polymer in slope reinforcement and field direct shear test - Changguang Qi; Mengqiang Shen; Zhichao Zhang; Junhao Li; Rufa Huang; Chaoxu Guo; Lijin Dong (Results in Engineering, 2025)
To enhance the basic properties of backfill soil in high slopes and improve its safety and stability, through dynamic compaction treatment of the fillers, the reinforcement research was conducted for the first time by combining polymer grouting and field direct shear tests. Field direct shear tests were conducted to measure the shear strength parameters of the backfill soil before and after grouting. The strength characteristics of the soil were compared before and after polymer grouting reinforcement. The results indicated that before grouting, the stress-displacement curve showed an initial increase followed by a stable phase. After grouting, the curve exhibited a stress peak, with the peak shear stress value increasing as the vertical stress increased. It was also found that higher grouting volumes corresponded to higher peak shear stress values, with the peak shear stress gradually shifting towards later stages and the shear failure time being delayed. After polymer grouting reinforcement, the soil's cohesion increased from 35.32 kPa before grouting to 70 kPa (0.2 g/cm3) and 90 kPa (0.3 g/cm3), the increase rates were 98.2 % and 155 % respectively, showing a significant increase in cohesion, while the internal friction angle remained relatively unchanged. In the direct shear tests of polymer-grouted reinforced soil, the soil was more compact due to the compaction effect of dynamic compaction, and the polymer columnar material was harder, resulting in less noticeable permeation and splitting grouting effects. The application of polymer grouting reinforcement in slope soil bodies has improved the overall shear strength of the slope soil, providing a reference for slope support engineering.